Flame-retardant modified composite plastic and preparation process thereof

By introducing nanosilica modified ABS and benzoxazine-based ring triphosphazene flame retardant intermediates into PC/ABS composite plastics, the problems of insufficient flame retardant, heat resistance and mechanical properties of existing composite plastics are solved. , achieving the performance improvement of composite plastics.

CN119463444AInactive Publication Date: 2025-02-18ZHONG LIANG ELECTRICAL IND (GUANGDONG) CO LTD

Patent Information

Application Number
CN202411515926.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The flame retardant properties, heat resistance and mechanical properties of existing PC/ABS composite plastics have not been effectively improved, which limits its use in high-demand applications.

Method used

Using nano-silicon dioxide modified ABS and benzoxazine-based cyclotriphosphazene flame retardant intermediates, the process of twin-screw extruder and injection molding machines was used to prepare excellent flame retardant, heat resistance and mechanical properties. composite plastic.

Benefits of technology

The flame retardant, heat resistance and mechanical properties of composite plastics are significantly improved, making them suitable for higher demanding application areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463444A_ABST
    Figure CN119463444A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ABS (Acrylonitrile Butadiene Styrene) plastics, and discloses a flame-retardant modified composite plastic and a preparation process thereof. 1, 2, 4-triaminobenzene, phosphonitrilic chloride trimer, 5-hydroxyisophthalonitrile and the like are used as raw materials to obtain a benzoxazinyl cyclotriphosphazene flame-retardant intermediate; the nano silicon dioxide modified ABS is prepared by taking maleic anhydride, allyltriethoxysilane and ABS as raw materials. And finally, uniformly mixing PC, ABS, the nano silicon dioxide modified ABS, the benzoxazine cyclotriphosphazene flame-retardant intermediate and the like, extruding and granulating, and carrying out injection molding to obtain the flame-retardant modified composite plastic. The composite plastic contains a benzoxazine structure, a cyano group, a benzene ring rigid structure and nano silicon dioxide rigid particles, so that the heat resistance of the composite plastic is improved. The synergistic effect of the phosphorus element, the nitrogen element and the nano silicon dioxide is utilized, so that the flame retardant property of the material is improved. The composite plastic prepared by the invention has excellent flame retardant property, heat resistance and mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ABS plastics, in particular to a flame retardant modified composite plastic and a preparation process thereof. Background Art

[0002] Acrylonitrile-butadiene-styrene plastic (ABS) is widely used in many fields due to its excellent comprehensive performance, high gloss, easy processing and other advantages. However, pure ABS is a flammable material, so it is necessary to modify ABS plastic to improve its flame retardant grade. Polycarbonate (PC) has the characteristics of high impact strength, good dimensional stability and excellent dielectric properties, but it has the disadvantages of poor processing fluidity and poor wear resistance. ABS has the characteristics of good processing performance. The PC / ABS plastic alloy obtained by blending the two combines the excellent mechanical properties and heat resistance of PC with the processing fluidity of ABS, making it widely used in the fields of automotive internal parts, machinery, household appliances, etc. However, the flame retardant properties of PC / ABS composite plastics have not been improved, so it needs to be modified to enhance its application range.

[0003] For example, the patent with authorization announcement number CN 113388222 B discloses a flame-retardant ABS composite material and a preparation method thereof. The invention uses ABS resin, PC resin, antioxidant, flame retardant, etc. as raw materials. The prepared composite material has the characteristics of high gloss and good flame retardant performance, but does not improve the heat resistance and mechanical properties of the flame-retardant ABS composite material. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a flame retardant modified composite plastic and a preparation process thereof. The prepared composite plastic has excellent flame retardant properties, heat resistance and mechanical properties.

[0005] To achieve the above object, the technical solution adopted by the present invention is: a flame retardant modified composite plastic, the flame retardant modified composite plastic comprises the following components in parts by weight: 100 parts by weight of PC, 5-20 parts by weight of ABS, 5-20 parts by weight of nano-silicon dioxide modified ABS, 1-15 parts by weight of benzoxazine-based cyclotriphosphazene flame retardant intermediate, 0.2-0.5 parts by weight of antioxidant, 0.3-0.5 parts by weight of anti-dripping agent;

[0006] The preparation process of flame retardant modified composite plastic is:

[0007] The dried PC and ABS are added into a double-roll mixer and mixed evenly, and then the nano-silica modified ABS, benzoxazine-based cyclotriphosphazene flame retardant intermediate, antioxidant and anti-dripping agent are added thereto, mixed thoroughly, placed in a twin-screw extruder for melt blending, granulated with a pelletizer, dried, and injection molded in an injection molding machine to obtain a flame retardant modified composite plastic.

[0008] Further preferably, the temperatures in each zone of the twin-screw extruder are 180°C, 230°C, 260°C, 260°C, and 250°C, the die temperature is 250°C, and the screw speed is 180 r / min.

[0009] Further preferably, the temperature of each section of the injection molding machine is 260° C., 265° C., and the injection pressure is 75 MPa.

[0010] Further preferably, the antioxidant is one of antioxidant 168 and antioxidant 1010; and the anti-dripping agent is polytetrafluoroethylene.

[0011] Further preferably, the preparation process of the nano-silicon dioxide modified ABS is:

[0012] S1, adding nano-silica to ethyl acetate solvent, ultrasonically dispersing, then adding allyl triethoxysilane and deionized water, stirring and reacting at 65-75° C. for 8-12 hours, washing with ethyl acetate after the reaction, and drying to obtain olefinated nano-silica;

[0013] S2. Add ABS to butyl acetate solvent, stir and dissolve at 85-95°C, add maleic anhydride, olefinated nano-silica and diisopropylbenzene peroxide, stir and disperse, heat to 110-120°C, stir and react for 5-10 hours, cool to room temperature after the reaction, add ethanol, filter, wash with ethanol, and dry to obtain nano-silica modified ABS.

[0014] Further preferably, in S1, the usage ratio of nano-silicon dioxide, allyltriethoxysilane and deionized water is (30-50) g: (300-400) g: 10 g.

[0015] Further preferably, in S2, the usage ratio of ABS, maleic anhydride, olefinic nano-silica, and dicumyl peroxide is 10 g:(1-1.5) g:(0.5-2) g:(0.05-0.2) g.

[0016] Further preferably, the preparation process of the benzoxazinyl cyclotriphosphazene flame retardant intermediate is:

[0017] (1) Under a nitrogen atmosphere, 1,2,4-triaminobenzene and hexachlorocyclotriphosphazene are added to a toluene solvent, stirred and dispersed, and triethylamine is added thereto. The temperature is raised to 100-110° C. and the reaction is carried out for 10-18 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered under reduced pressure, washed with deionized water, washed with tetrahydrofuran, and dried to obtain an intermediate 1;

[0018] (2) Add the intermediate 1, 5-hydroxyisophthalonitrile and polyformaldehyde to a toluene solvent, stir and disperse, react at 100-110° C. for 4-8 hours, and after the reaction is completed, cool to room temperature, wash with a 0.1 mol / L sodium hydroxide aqueous solution, rotary evaporate, and dry to obtain a benzoxazine-based cyclotriphosphazene flame retardant intermediate.

[0019] More preferably, in (1), the usage ratio of 1,2,4-triaminobenzene, hexachlorocyclotriphosphazene and triethylamine is (10-15) g:10 g:(18-20) g.

[0020] More preferably, in (2), the usage ratio of the intermediate 1, 5-hydroxyisophthalonitrile, and polyformaldehyde is 10 g:(8.6-10) g:(4-6) g.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The invention uses 1,2,4-triaminobenzene, hexachlorocyclotriphosphazene, 5-hydroxyisophthalonitrile and polyformaldehyde as starting materials, and obtains a benzoxazinylcyclotriphosphazene flame retardant intermediate through two-step reaction. The preparation method is simple and the structure is relatively novel. Maleic anhydride and allyltriethoxysilane are used as grafting monomers and grafted onto ABS to obtain nano-silicon dioxide modified ABS. Finally, PC, ABS, nano-silicon dioxide modified ABS, benzoxazinylcyclotriphosphazene flame retardant intermediate and the like are uniformly mixed, extruded into granules, and injection molded to obtain a flame retardant modified composite plastic.

[0023] The composite plastic prepared by the present invention contains a benzoxazine structure and a cyano structure. The benzoxazine structure absorbs heat when heated and opens the ring to form a cross-linked network structure, thereby improving the high temperature resistance of the material. The cyano group therein absorbs heat when heated to form highly cross-linked structures such as triazine rings and phthalocyanine rings, thereby further improving the high temperature resistance of the composite plastic. In addition, the rigid benzene ring structure and the rigid nano-silicon dioxide particles contained therein can also absorb heat and improve the heat resistance of the composite plastic.

[0024] The composite plastic prepared by the present invention contains phosphorus, which generates phosphoric acid structure during heating and forms pyrophosphate group through dehydration, both of which can promote the dehydration reaction of the material to form a dense carbon layer on the surface of the material, which has a good effect of blocking heat and oxygen, thereby achieving a flame retardant effect; the nitrogen element generates a carbon foam layer on the surface of the plastic when heated, and releases non-flammable gas to dilute the content of flammable gas in the air, thereby achieving the purpose of flame retardancy. In addition, inorganic nanoparticles such as nano-silicon dioxide contained therein can also improve the flame retardant properties of the composite plastic, and the three act synergistically to jointly improve the flame retardant properties of the material.

[0025] The composite material prepared by the present invention contains nano silicon dioxide, which is easy to agglomerate. The present invention makes it organic, increases its compatibility with organic substances, and can be evenly dispersed in the composite plastic. When it is impacted, it can serve as a stress concentration point to absorb energy and improve the mechanical properties of the composite plastic. The composite plastic prepared by the present invention has excellent flame retardant properties, heat resistance and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a preparation route for benzoxazinyl cyclotriphosphazene flame retardant intermediates. DETAILED DESCRIPTION

[0027] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0028] Example 1

[0029] (1) Under a nitrogen atmosphere, 10.4 g of 1,2,4-triaminobenzene and 10.4 g of hexachlorocyclotriphosphazene were added to 200 mL of toluene solvent, stirred and dispersed, and then 20.8 g of triethylamine was added thereto. The temperature was raised to 105° C. and the reaction was carried out for 12 h. After the reaction was completed, the mixture was cooled to room temperature, filtered under reduced pressure, washed with deionized water, washed with tetrahydrofuran, and dried to obtain intermediate 1.

[0030] (2) Add 25 g of intermediate 1, 24 g of 5-hydroxyisophthalonitrile, and 12 g of polyformaldehyde to 200 mL of toluene solvent, stir and disperse, and react at 110° C. for 6 h. After the reaction is completed, cool to room temperature, wash with 0.1 mol / L sodium hydroxide aqueous solution, rotary evaporate, and dry to obtain a benzoxazine-based cyclotriphosphazene flame retardant intermediate.

[0031] (3) 4 g of nano-silica was added to 200 mL of ethyl acetate solvent and dispersed by ultrasonication. Then, 35 g of allyltriethoxysilane and 1 g of deionized water were added thereto. The mixture was stirred at 75° C. for 8 h. After the reaction was completed, the mixture was washed with ethyl acetate and dried to obtain olefinated nano-silica.

[0032] (4) 10 g of ABS was added to 250 mL of butyl acetate solvent, stirred and dissolved at 95° C., 1.2 g of maleic anhydride, 0.5 g of olefinated nano-silica, and 0.1 g of diisopropylbenzene peroxide were added thereto, stirred and dispersed, and the temperature was raised to 115° C. and stirred for reaction for 10 h. After the reaction was completed, the mixture was cooled to room temperature, ethanol was added thereto, filtered, washed with ethanol, and dried to obtain nano-silica modified ABS.

[0033] (5) 20 g of dried PC and 1 g of ABS were added to a double-roll mixer and mixed evenly. Then, 1 g of nano-silica modified ABS, 0.2 g of benzoxazinyl cyclotriphosphazene flame retardant intermediate, 0.04 g of antioxidant 1010, and 0.1 g of polytetrafluoroethylene anti-dripping agent were added thereto, mixed thoroughly, and placed in a twin-screw extruder for melt blending. The temperatures of each zone of the twin-screw extruder were 180°C, 230°C, 260°C, 260°C, and 250°C, the head temperature was 250°C, the screw speed was 180 r / min, the pelletizer was used for granulation, the pelletizer was dried, and the pellets were injection molded in an injection molding machine. The temperatures of each section of the injection molding machine were 260°C and 265°C, and the injection molding pressure was 75 MPa to obtain a flame retardant modified composite plastic.

[0034] Example 2

[0035] (1) Under a nitrogen atmosphere, 12.3 g of 1,2,4-triaminobenzene and 10.4 g of hexachlorocyclotriphosphazene were added to 200 mL of toluene solvent, stirred and dispersed, and then 18.7 g of triethylamine was added thereto. The temperature was raised to 110° C. and the reaction was carried out for 10 h. After the reaction was completed, the mixture was cooled to room temperature, filtered under reduced pressure, washed with deionized water, washed with tetrahydrofuran, and dried to obtain intermediate 1.

[0036] (2) Add 25 g of intermediate 1, 22 g of 5-hydroxyisophthalonitrile, and 15 g of polyformaldehyde to 200 mL of toluene solvent, stir and disperse, and react at 100° C. for 8 h. After the reaction is completed, cool to room temperature, wash with 0.1 mol / L sodium hydroxide aqueous solution, rotary evaporate, and dry to obtain a benzoxazine-based cyclotriphosphazene flame retardant intermediate.

[0037] (3) 3 g of nano-silica was added to 200 mL of ethyl acetate solvent and ultrasonically dispersed. Then, 30 g of allyltriethoxysilane and 1 g of deionized water were added thereto. The mixture was stirred and reacted at 65° C. for 10 h. After the reaction was completed, the mixture was washed with ethyl acetate and dried to obtain olefinated nano-silica.

[0038] (4) 10 g of ABS was added to 250 mL of butyl acetate solvent, stirred and dissolved at 85° C., 1 g of maleic anhydride, 1 g of olefinated nano-silica, and 0.05 g of diisopropylbenzene peroxide were added thereto, and the mixture was dispersed by stirring. The mixture was heated to 110° C. and stirred for reaction for 5 h. After the reaction was completed, the mixture was cooled to room temperature, ethanol was added thereto, filtered, washed with ethanol, and dried to obtain nano-silica modified ABS.

[0039] (5) 20 g of dried PC and 3 g of ABS were added to a twin-roll mixer and mixed evenly. Then, 2 g of nano-silica modified ABS, 1 g of benzoxazinyl cyclotriphosphazene flame retardant intermediate, 0.1 g of antioxidant 168, and 0.06 g of polytetrafluoroethylene anti-dripping agent were added thereto, mixed thoroughly, and placed in a twin-screw extruder for melt blending. The temperatures of each zone of the twin-screw extruder were 180°C, 230°C, 260°C, 260°C, and 250°C, the head temperature was 250°C, the screw speed was 180 r / min, the pelletizer was used for granulation, the pelletizer was dried, and the pellets were injection molded in an injection molding machine. The temperatures of each section of the injection molding machine were 260°C and 265°C, and the injection molding pressure was 75 MPa to obtain a flame retardant modified composite plastic.

[0040] Example 3

[0041] (1) Under a nitrogen atmosphere, 14.6 g of 1,2,4-triaminobenzene and 10.4 g of hexachlorocyclotriphosphazene were added to 200 mL of toluene solvent, stirred and dispersed, and then 20.2 g of triethylamine was added thereto. The temperature was raised to 100° C. and the reaction was carried out for 18 h. After the reaction was completed, the mixture was cooled to room temperature, filtered under reduced pressure, washed with deionized water, washed with tetrahydrofuran, and dried to obtain intermediate 1.

[0042] (2) Add 25 g of intermediate 1, 21.5 g of 5-hydroxyisophthalonitrile, and 12 g of polyformaldehyde to 200 mL of toluene solvent, stir and disperse, and react at 105° C. for 6 h. After the reaction is completed, cool to room temperature, wash with 0.1 mol / L sodium hydroxide aqueous solution, rotary evaporate, and dry to obtain a benzoxazine-based cyclotriphosphazene flame retardant intermediate.

[0043] (3) 5 g of nano-silica was added to 200 mL of ethyl acetate solvent and dispersed by ultrasonication. Then, 40 g of allyltriethoxysilane and 1 g of deionized water were added thereto. The mixture was stirred at 65° C. for 12 h. After the reaction was completed, the mixture was washed with ethyl acetate and dried to obtain olefinated nano-silica.

[0044] (4) 10 g of ABS was added to 250 mL of butyl acetate solvent, stirred and dissolved at 95° C., 1.5 g of maleic anhydride, 1.5 g of olefinated nano-silica, and 0.1 g of diisopropylbenzene peroxide were added thereto, stirred and dispersed, and the temperature was raised to 120° C. and stirred for reaction for 10 h. After the reaction was completed, the mixture was cooled to room temperature, ethanol was added thereto, filtered, washed with ethanol, and dried to obtain nano-silica modified ABS.

[0045] (5) 20 g of dried PC and 4 g of ABS were added to a two-roll mixer and mixed evenly. Then, 3 g of nano-silica modified ABS, 2 g of benzoxazinyl cyclotriphosphazene flame retardant intermediate, 0.1 g of antioxidant 168, and 0.1 g of polytetrafluoroethylene anti-dripping agent were added thereto, mixed thoroughly, and placed in a twin-screw extruder for melt blending. The temperatures of each zone of the twin-screw extruder were 180°C, 230°C, 260°C, 260°C, and 250°C, the head temperature was 250°C, the screw speed was 180 r / min, the pelletizer was used for granulation, the pelletizer was dried, and the pellets were injection molded in an injection molding machine. The temperatures of each section of the injection molding machine were 260°C and 265°C, and the injection molding pressure was 75 MPa to obtain a flame retardant modified composite plastic.

[0046] Example 4

[0047] (1) Under a nitrogen atmosphere, 14 g of 1,2,4-triaminobenzene and 10.4 g of hexachlorocyclotriphosphazene were added to 200 mL of toluene solvent, stirred and dispersed, and then 18 g of triethylamine was added thereto. The temperature was raised to 105° C. and the reaction was carried out for 18 h. After the reaction was completed, the mixture was cooled to room temperature, filtered under reduced pressure, washed with deionized water, washed with tetrahydrofuran, and dried to obtain intermediate 1.

[0048] (2) Add 25 g of intermediate 1, 25 g of 5-hydroxyisophthalonitrile, and 10 g of polyformaldehyde to 200 mL of toluene solvent, stir and disperse, and react at 110° C. for 4 h. After the reaction is completed, cool to room temperature, wash with 0.1 mol / L sodium hydroxide aqueous solution, rotary evaporate, and dry to obtain a benzoxazine-based cyclotriphosphazene flame retardant intermediate.

[0049] (3) 5 g of nano-silica was added to 200 mL of ethyl acetate solvent and ultrasonically dispersed. Then, 30 g of allyltriethoxysilane and 1 g of deionized water were added thereto. The mixture was stirred at 70° C. for 10 h. After the reaction was completed, the mixture was washed with ethyl acetate and dried to obtain olefinated nano-silica.

[0050] (4) 10 g of ABS was added to 250 mL of butyl acetate solvent, stirred and dissolved at 90° C., 1 g of maleic anhydride, 2 g of olefinated nano-silica, and 0.2 g of diisopropylbenzene peroxide were added thereto, stirred and dispersed, and the temperature was raised to 115° C. and stirred for reaction for 6 h. After the reaction was completed, the mixture was cooled to room temperature, ethanol was added thereto, filtered, washed with ethanol, and dried to obtain nano-silica modified ABS.

[0051] (5) 20 g of dried PC and 2 g of ABS were added to a twin-roll mixer and mixed evenly. Then, 4 g of nano-silica modified ABS, 3 g of benzoxazinyl cyclotriphosphazene flame retardant intermediate, 0.05 g of antioxidant 1010, and 0.1 g of polytetrafluoroethylene anti-dripping agent were added thereto, mixed thoroughly, and placed in a twin-screw extruder for melt blending. The temperatures of each zone of the twin-screw extruder were 180°C, 230°C, 260°C, 260°C, and 250°C, the head temperature was 250°C, the screw speed was 180 r / min, the pelletizer was used for granulation, the pelletizer was dried, and the pellets were injection molded in an injection molding machine. The temperatures of each section of the injection molding machine were 260°C and 265°C, and the injection molding pressure was 75 MPa to obtain a flame retardant modified composite plastic.

[0052] Comparative Example 1

[0053] The difference between this comparative example and Example 1 is that step (5) does not contain nano-silicon dioxide-modified ABS.

[0054] Comparative Example 2

[0055] The difference between this comparative example and Example 1 is that step (5) does not contain benzoxazine-based cyclotriphosphazene flame retardant intermediate.

[0056] Use oxygen index meter to test the limiting oxygen index of composite plastics. The standard sample size is 150×10×4mm 3 .

[0057] The vertical combustion level of composite plastics is tested using a horizontal vertical combustion test chamber. The standard sample size is 127×12.7×3.2mm 3 .

[0058] Table 1:

[0059]

[0060]

[0061] It can be seen from the table that the composite plastic prepared by the present invention has excellent flame retardant properties.

[0062] The heat deformation temperature of the material was tested according to ISO75-1-2013, with a load of 1.8 MPa and a heating rate of 120°C / h.

[0063] Table 2:

[0064] Heat deformation temperature / ℃ Example 1 127 Example 2 133 Example 3 137 Example 4 135 Comparative Example 1 125 Comparative Example 2 118

[0065] The higher the heat deformation temperature, the better the heat resistance. It can be seen from the table that the composite plastic prepared by the present invention has excellent heat resistance.

[0066] The tensile strength of composite plastics was tested using a universal testing machine. The standard specimen size was 120×10×4mm. 3 .

[0067] The notched impact strength of composite plastics was tested using a pendulum impact tester. The standard specimen size was 62.5×12.7×4mm. 3 .

[0068] Table 3:

[0069]

[0070]

[0071] It can be seen from the table that the composite plastic prepared by the present invention has good mechanical properties.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A flame retardant modified composite plastic, characterized in that: The flame retardant modified composite plastic comprises the following components in parts by weight: 100 parts by weight of PC, 5-20 parts by weight of ABS, 5-20 parts by weight of nano-silicon dioxide modified ABS, 1-15 parts by weight of benzoxazine-based cyclotriphosphazene flame retardant intermediate, 0.2-0.5 parts by weight of antioxidant, and 0.3-0.5 parts by weight of anti-dripping agent; The preparation process of flame retardant modified composite plastic is: The dried PC and ABS are added into a double-roll mixer and mixed evenly, and then the nano-silica modified ABS, benzoxazine-based cyclotriphosphazene flame retardant intermediate, antioxidant and anti-dripping agent are added thereto, mixed thoroughly, placed in a twin-screw extruder for melt blending, granulated with a pelletizer, dried, and injection molded in an injection molding machine to obtain a flame retardant modified composite plastic.

2. The flame retardant modified composite plastic according to claim 1, characterized in that: The temperatures of the zones of the twin-screw extruder are 180° C., 230° C., 260° C., 260° C., and 250° C., the die head temperature is 250° C., and the screw speed is 180 r / min.

3. The flame retardant modified composite plastic according to claim 1, characterized in that: The temperatures of each section of the injection molding machine are 260° C. and 265° C., and the injection pressure is 75 MPa.

4. The flame retardant modified composite plastic according to claim 1, characterized in that: The antioxidant is one of antioxidant 168 and antioxidant 1010; the anti-dripping agent is polytetrafluoroethylene.

5. The flame retardant modified composite plastic according to claim 1, characterized in that: The preparation process of the nano-silicon dioxide modified ABS is as follows: S1, adding nano-silica to ethyl acetate solvent, ultrasonically dispersing, then adding allyl triethoxysilane and deionized water, stirring and reacting at 65-75° C. for 8-12 hours, washing with ethyl acetate after the reaction, and drying to obtain olefinated nano-silica; S2. Add ABS to butyl acetate solvent, stir and dissolve at 85-95°C, add maleic anhydride, olefinated nano-silica and diisopropylbenzene peroxide, stir and disperse, heat to 110-120°C, stir and react for 5-10 hours, cool to room temperature after the reaction, add ethanol, filter, wash with ethanol, and dry to obtain nano-silica modified ABS.

6. The flame retardant modified composite plastic according to claim 5, characterized in that: In the S1, the usage ratio of nano-silicon dioxide, allyltriethoxysilane and deionized water is (30-50) g: (300-400) g: 10 g.

7. The flame retardant modified composite plastic according to claim 5, characterized in that: In the S2, the usage ratio of ABS, maleic anhydride, olefinic nano-silica and dicumyl peroxide is 10g:(1-1.5)g:(0.5-2)g:(0.05-0.2)g.

8. The flame retardant modified composite plastic according to claim 1, characterized in that: The preparation process of the benzoxazinyl cyclotriphosphazene flame retardant intermediate is as follows: (1) Under a nitrogen atmosphere, 1,2,4-triaminobenzene and hexachlorocyclotriphosphazene are added to a toluene solvent, stirred and dispersed, and triethylamine is added thereto. The temperature is raised to 100-110° C. and the reaction is carried out for 10-18 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered under reduced pressure, washed with deionized water, washed with tetrahydrofuran, and dried to obtain an intermediate 1; (2) Add the intermediate 1, 5-hydroxyisophthalonitrile and polyformaldehyde to a toluene solvent, stir and disperse, react at 100-110° C. for 4-8 hours, and after the reaction is completed, cool to room temperature, wash with a 0.1 mol / L sodium hydroxide aqueous solution, rotary evaporate, and dry to obtain a benzoxazine-based cyclotriphosphazene flame retardant intermediate.

9. The flame retardant modified composite plastic according to claim 8, characterized in that: In the above (1), the usage ratio of 1,2,4-triaminobenzene, hexachlorocyclotriphosphazene and triethylamine is (10-15) g:10 g:(18-20) g.

10. The flame retardant modified composite plastic according to claim 8, characterized in that: In the above (2), the usage ratio of the intermediate 1, 5-hydroxyisophthalonitrile and polyformaldehyde is 10g:(8.6-10)g:(4-6)g.

Citation Information

Patent Citations

  • A flame-retardant ABS composite material and its preparation method

    CN113388222B

Cited By

  • Halogen-free flame-retardant PC / ABS material and preparation method thereof

    CN120988447A